(3GdefUas - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s; (3HcQ Hf eMeO Hf MHjH Hf HbjI GdeGRfj, CHh YKeGf,J (B249 (3g` s
(3ChdgG (B:s
(3Ef GHfG ef GdfHhI hGddGe ajg hGh dCf eDfKg HfJ s
(3BNQgG (B:s
(3bGd CHhGdaJM (B: (3GYde Cfg bO cGf GdbjGS Cf jgR GdghGeR ai cd bhd dCf GdCda bO GcJfagG hGhGf s
(3bWYI ef GdeNWhWs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B18 - (3U (B403 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B412s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas